Efek Inovasi Penyinaran Lampu Pada Usahatani Buah Naga di Desa Bulurejo Kecamatan Purwoharjo Kabupaten Banyuwangi - Indra Dwi Susanto; Mohammad Rondhi (Jurnal KIRANA, 2020)
Dragon fruit is a type of cactus plant that is cultivated in Indonesia and is included in an annual plant because it can only bear fruit during the rainy season. One of the largest dragon fruit producing areas in Indonesia is located in Banyuwangi Regency, East Java. Bulurejo Village is the area that uses the most innovation in lighting lighting. The use of innovative light irradiation is able to develop dragon fruit plants so that dragon fruit plants can bear fruit outside the season. Research in Bulurejo Village, Purwoharjo District, Banyuwangi Regency aims: (1) To determine farming with the use of light illumination innovation in Bulurejo Village, Purwoharjo District, Banyuwangi Regency, (2) To determine the effect of innovative lighting effects on dragon fruit farming in Bulurejo Village, Purwoharjo District, Banyuwangi Regency . The determination of the research area was done purposively (purposive method). The research area used is Bulurejo Village, Purwoharjo District, Banyuwangi Regency. The sampling method in this study uses the determination of key informants using purposive sampling technique, which is selected with certain considerations and goals. The results showed that: (1) The existence of innovative lighting on dragon fruit plants in Bulurejo Village was well received by farmers and the community. The use of innovation in Bulurejo Village is able to increase the productivity of dragon fruit farmers to the maximum, (2) The effect of using light irradiation innovation on dragon fruit plants is very good for farmers economically as well as socially and culturally in the community. The increasing economic condition of dragon fruit farmers with large incomes has been able to increase the standard of living of farmers who were initially normal to become successful dragon fruit farmers. The social and cultural conditions of the community are also getting more harmonious after the innovation of lighting the lights. Keywords: Dragon Fruit, Bulurejo Farmer, Lightning Innovation, Social Effect